INTERNALISASI NILAI KEPEMIMPINAN ARJUNA DALAM MAHABHARATA SEBAGAI STRATEGI PENGUATAN PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR DI SDN 4 SIBANGKAJA, BADUNG, BALI - I Nengah Arimbawa (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2026)
Strengthening character education for elementary school students is an urgent need in today's digital era. Rapid technological developments bring new challenges such as learning distractions, low concentration, verbal aggressiveness, and declining moral role models. Considering the challenges of the digital era that give rise to impulsive behaviour, low discipline, and weakened moral role models, the integration of classical cultural values ​​​​is one solution to contextual character education. One potential approach is the use of classical literature, particularly the Mahabharata epic, which has high educational value. This study aims to describe the internalization of Arjuna's leadership values ​​​​in the Mahabharata as a strategy for character formation of elementary school students at Sibangkaja 4 Public Elementary School, Badung, Bali. The research method used a qualitative descriptive approach through text analysis, interviews with six upper-grade teachers of Sibangkaja 4 Public Elementary School, and observation of Itihasa-based teaching materials. The results show that Arjuna's leadership values ​​​​such as discipline, focus, self-control, humility, and wisdom in decision-making can be integrated into thematic learning, literacy, character education, and the Pancasila Student Profile project. This study concludes that the character of Arjuna is a worthy role model in the context of character education because he possesses universal values ​​appropriate to child development and closely aligns with local Balinese culture. This study recommends the development of a Mahabharata learning module for children, teacher training, and the enhancement of culture-based interactive digital media.